2010
DOI: 10.1016/j.crohns.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of activity of Crohn's disease by Doppler sonography of superior mesenteric artery flow

Abstract: Doppler sonographic parameters of superior mesenteric artery are significantly correlated with disease activity in non-operated and non-complicated Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Our study showed no significant difference in PSV and EDV values between active and inactive CD, but we found a significant difference in RI values in mural arteries. Higher values of flow volume and lower RI of mural arteries in thickened bowel wall were recorded in different studies 22,24,25. The probable reason is arterial hyperemia in the thickened gut wall of Crohn’s disease.…”
Section: Discussionmentioning
confidence: 88%
“…Our study showed no significant difference in PSV and EDV values between active and inactive CD, but we found a significant difference in RI values in mural arteries. Higher values of flow volume and lower RI of mural arteries in thickened bowel wall were recorded in different studies 22,24,25. The probable reason is arterial hyperemia in the thickened gut wall of Crohn’s disease.…”
Section: Discussionmentioning
confidence: 88%
“…Vascularity within the bowel walls has been evaluated using a subjective scoring system according to the intensity of color signals and/or by the measurement of resistive index obtained from vessels detected within the bowel walls. [62][63][64][65][66][67][68] Ten studies including a total of 446 patients with established CD were identified 45,48,53,[55][56][57][58][59]61,62 (Table 6). All studies considered CDAI as reference standard and 3 studies used endoscopy as standard for disease activity.…”
Section: Assessment Of Disease Activitymentioning
confidence: 99%
“…A literature review revealed that CDUS examination of the SMA has been used to determine Crohn disease activity or intestinal inflammation caused by other illnesses, bowel wall perfusion in preterm neonates to predict developing necrotizing enterocolitis, or in children with small bowel obstruction for the detection of strangulation (8,14,15). In the present study we intended to evaluate SMA blood flow hemodynamics after surgery and found low values of SMA BFV, PSV, and RI when assessed with the cut-off values given in the literature (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%